Elastic pad and electrolyzer
By using a conductive elastic pad of a specific shape in the electrolytic cell, the problem of damage to the ion exchange membrane caused by excessive surface pressure in the prior art is solved, and the high reverse pressure difference resistance and film protection are achieved.
Patent Information
- Application Number
- CN202080014216.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-03-18
- Filing Date
- 2020-03-18
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2040-03-18
AI Technical Summary
In the prior art, although the elastic pad can maintain a zero-distance structure when used in an electrolytic cell, excessive surface pressure may lead to damage to the ion exchange membrane, making it difficult to take into account both the reverse pressure difference resistance and the membrane protection.
Using conductive elastic pads with a specific shape, a plurality of peaks and valleys are formed by bending, and concaves and convexes are formed on the peaks and valleys to ensure that the elastic pads can effectively absorb stress under the reverse pressure difference, while reducing Commonly used surface pressure.
It is realized that the common surface pressure is provided in the electrolytic cell to prevent damage to the ion exchange membrane, while maintaining high reverse pressure differential resistance, ensuring the stable operation of the electrolytic cell.
Smart Images

Figure CN113474491B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an elastic pad and an electrolytic cell. Background Art
[0002] In electrolysis using an aqueous solution of alkali metal chloride such as saline (hereinafter referred to as "electrolysis"), an ion exchange membrane method is used. The ion exchange membrane method uses an electrolytic cell equipped with an ion exchange membrane. As an electrolytic cell used in electrolysis, in order to reduce the distance between electrodes, an electrolytic cell in the form of a thin solid electrolyte membrane substantially sandwiched between positive and negative electrodes, i.e., a so-called zero-gap electrolytic cell, has been proposed.
[0003] In a zero-gap electrolyzer, by making at least one component that clamps the ion exchange membrane an elastic component, even when pressure changes occur in the electrolytic cell, the elastic component can be used to absorb stress that may cause damage to the ion exchange membrane. As an example of such an elastic component, Patent Document 1 discloses a scheme of using the following cushion as an elastic cushion, which is a cushion in the form of a fabric made of four 0.1 mm nickel wires, and further processed into a corrugated shape to have a thickness of 9 mm.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 5047265 Summary of the invention
[0007] Problems to be solved by the invention
[0008] For the elastic pad, it is required that its shape can be maintained to a degree that can maintain zero spacing (will not be crushed) even if it is subjected to a certain degree of reverse pressure difference. The property that represents the residual ease of the thickness of the elastic pad when the load is released after being exposed to the reverse pressure difference like this is called reverse pressure difference resistance. Under the premise of being applied to the zero-spacing electrolytic cell, the reverse pressure difference resistance of the elastic pad is preferably high. For example, it is known that sufficient reverse pressure difference resistance can be ensured by increasing the rebound force of the elastic pad. However, when the rebound force of the elastic pad is increased, that is, a strong elastic pad is made, the surface pressure (also referred to as "common surface pressure" in this specification) applied by the elastic pad during the operation of the electrolytic cell also tends to increase. Commonly used high surface pressure means that the load applied to the ion exchange membrane is high, so the possibility of membrane damage will increase. Here, the elastic pad described in Patent Document 1 is made by processing the fabric of nickel wire into a waveform. For example, by stacking it in multiple layers for use, the reverse pressure difference resistance can be further improved and it can be not easily crushed, but at the same time, the surface pressure during common use tends to increase. That is, in the technology of Patent Document 1, the ion exchange membrane may be damaged due to excessive increase in the surface pressure during normal use. Thus, in the prior art, when pressure fluctuations occur in the electrolytic cell, there is a trade-off between maintaining the zero-gap structure and preventing membrane damage. That is, the elastic pad described in Patent Document 1 still has room for further improvement from the perspective of appropriate normal surface pressure, and an elastic pad that can balance maintaining the zero-gap structure and preventing membrane damage is being sought.
[0009] The present invention has been made in view of the above-mentioned problems of the prior art, and its object is to provide an elastic pad and an electrolytic cell which can provide a moderate normal surface pressure when used in an electrolytic cell, can prevent damage to the ion exchange membrane, and has excellent resistance to reverse pressure difference.
[0010] Means for solving problems
[0011] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that the above-mentioned problems can be solved by using an elastic pad having a specific shape or an elastic pad having specific parameters, thereby completing the present invention.
[0012] That is, the present invention is as follows. [1]
[0014] An elastic pad is an elastic pad having conductivity, wherein:
[0015] The elastic pad has a plurality of peaks and valleys formed by bending.
[0016] The peak has a concave portion having a depth smaller than the height of the peak,
[0017] The valley portion has a convex portion having a height smaller than a depth of the valley portion. [2]
[0019] An elastic pad as described in [1], wherein:
[0020] The formation direction of a peak is approximately parallel to the formation direction of the adjacent peak.
[0021] The formation direction of one valley portion and the formation direction of the adjacent valley portion are both substantially parallel to each other. [3]
[0023] The elastic pad as described in [1] or [2], wherein the peaks and valleys are provided with a herringbone pattern in the surface direction of the elastic pad. [4]
[0025] The elastic pad as described in [3], wherein the inflection point in the herringbone pattern is one point, and the angle at the inflection point is greater than 90°. [5]
[0027] The elastic pad according to any one of [1] to [4], which is folded at an arbitrary position. [6]
[0029] An electrolytic cell comprising:
[0030] an anode chamber containing an anode;
[0031] A cathode chamber comprising the elastic pad described in any one of [1] to [5], a current collector, and a cathode; and
[0032] an ion exchange membrane disposed between the anode chamber and the cathode chamber,
[0033] In the cathode chamber, the elastic pad is disposed between the current collector and the cathode.
[0034] The elastic pad applies pressure to the cathode in a direction toward the ion exchange membrane. [7]
[0036] An elastic pad is an elastic pad having conductivity, wherein:
[0037] The thickness of the elastic pad is greater than 2 mm.
[0038] (i) the repulsive force of the elastic pad measured when pressed so that the thickness of the elastic pad becomes 2 mm is not less than 5 kPa and not more than 30 kPa,
[0039] (ii) The elastic pad is compressed at a pressure of 40 kPa for 20 seconds and then has a thickness of 1 mm or more when the pressure is released.
[0040] Effects of the Invention
[0041] The elastic pad of the present invention can provide a moderate normal surface pressure when applied to an electrolytic cell, thereby preventing damage to the ion exchange membrane and achieving high reverse pressure difference resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 It is a perspective schematic diagram showing an example of the elastic pad according to the present embodiment.
[0043] Figure 2 is corresponding to Figure 1 Schematic diagram of a partial cross section of the XX' section.
[0044] Figure 3 This is a perspective schematic diagram showing an example of a mode in which the elastic pad according to the present embodiment has a herringbone pattern.
[0045] Figure 4 It is a schematic cross-sectional view showing an example of an electrolytic cell to which the elastic pad of the present embodiment is applied.
[0046] Figure 5 Yes Figure 4 An explanatory diagram of a case where two electrolytic cells are connected in series.
[0047] Figure 6 This is an explanatory diagram showing an example of the electrolytic cell according to the present embodiment.
[0048] Figure 7 This is an explanatory diagram showing an example of the process of assembling the electrolytic cell according to the present embodiment.
[0049] Figure 8 (a) is an explanatory diagram for explaining a method for measuring the height of the peaks, the depth of the recesses, the depth of the valleys, and the height of the protrusions of the elastic pad in the examples. Figure 8 (b) corresponds to Figure 8 (a) Schematic diagram of a partial cross section of the XX' section.
[0050] Fig. 9 It is a partial cross-sectional schematic diagram showing the operation of assembling the elastic pad of Example 1 into an electrolytic cell.
[0051] Fig.10 Graph showing the relationship between the thickness of the elastic pad of Example 1 and the elastic pad of Comparative Example 1 and the contact surface pressure.
[0052] Fig.11 It is an explanatory diagram showing the structure of the elastic pad of Example 7.
[0053] Fig.12 It is an explanatory diagram showing the structure of the elastic pad of Example 8. DETAILED DESCRIPTION
[0054] The specific implementation mode of the present invention (hereinafter referred to as "this implementation mode") is described in detail below. It should be noted that the present invention is not limited to the following implementation mode, and can be implemented by various modifications within the scope of its main points. It should be noted that, unless otherwise stated, the positional relationships such as up, down, left, and right in the drawings are based on the positional relationships shown in the drawings. In addition, the dimensional ratios of the drawings are not limited to the ratios shown in the drawings.
[0055] [Elastic pad]
[0056] The elastic pad of the first mode of the present embodiment (hereinafter also referred to as "the first elastic pad") is an elastic pad having conductivity, and the elastic pad has a plurality of peaks and valleys formed by bending, the peaks having a concave portion having a depth smaller than the height of the peaks, and the valleys having a convex portion having a height smaller than the depth of the valleys. As described above, the first elastic pad is not simply a shape having peaks and valleys (a simple wave shape), but is configured in such a way that the peaks have concave portions and the valleys have convex portions, respectively. Therefore, while improving the resistance to reverse pressure difference, the normal surface pressure can be appropriately reduced. Therefore, when applied to an electrolytic cell, an appropriate normal surface pressure can be provided to prevent damage to the ion exchange membrane.
[0057] In addition, the elastic pad of the second mode of the present embodiment (hereinafter also referred to as the "second elastic pad") is an elastic pad having conductivity, wherein the thickness of the elastic pad is greater than 2 mm, (i) the repulsion force of the elastic pad measured when pressed in a manner such that the thickness of the elastic pad becomes 2 mm is 5 kPa or more and 30 kPa or less, and (ii) the thickness of the elastic pad when the pressure is released after the elastic pad is compressed at a pressure of 40 kPa for 20 seconds is greater than 1 mm. In the second elastic pad, as described above, since the specific parameters are within the specific range, the normal surface pressure can be appropriately reduced while improving the reverse pressure difference resistance, so when applied to the electrolytic cell, a moderate normal surface pressure can be provided to prevent damage to the ion exchange membrane.
[0058] Hereinafter, unless otherwise stated, the term “elastic pad according to the present embodiment” includes the first elastic pad and the second elastic pad.
[0059] When electrolysis is performed, it is usually preferred to place an elastic pad between the current collector and the cathode so that electricity is transmitted to the cathode and the hydrogen generated by the cathode passes through the current collector side without resistance. In addition, at this time, it is preferred to apply appropriate pressure evenly and to a degree that does not cause membrane damage to the cathode in contact with the ion exchange membrane, so that the ion exchange membrane and the cathode are closely fitted to perform the function. It is preferred to appropriately adjust the material and size of the elastic pad from such an aspect.
[0060] Regarding the conductivity of the elastic pad of the present embodiment, it is sufficient that the conductivity is at a level that can ensure electrical connection with the adjacent current collector when the elastic pad is applied to a zero-gap electrolytic cell. For example, it can be made conductive by using a metal material or other conductive materials. As the metal material, nickel, iron, cobalt, molybdenum, lead, their alloys, etc. can be used, but are not limited to these. From the aspects of conductivity and resistance to electrolytes and electrolysis products, nickel is preferred.
[0061] In the present embodiment, for example, an elastic pad precursor in the shape of a buffer pad can be formed by using an aggregate of wires (metal wires) made of the above metal materials, preferably by preparing multiple such metal wires and weaving them. The wire diameter of the wire in this case is not particularly limited and can be various wire diameters. From the aspects that the buffer pad is not easily crushed and the pressing pressure on the ion exchange membrane is not excessive, the wire diameter is preferably 0.05 mm to 0.25 mm. In addition, from the aspects of more easily preventing membrane damage by reducing the probability of wire breakage and effectively preventing the occurrence of uneven surface pressure by sufficiently ensuring the stiffness of the wire, the wire diameter is more preferably 0.10 mm to 0.25 mm, further preferably 0.15 mm to 0.25 mm, still further preferably 0.16 mm to 0.25 mm, and even more preferably 0.16 mm to 0.19 mm.
[0062] The weaving method of the wire is not particularly limited, and various known weaving methods can be adopted. In the present embodiment, for example, knitting can be adopted.
[0063] The first elastic pad is formed in a form in which the above elastic pad precursor is bent in the thickness direction to have a plurality of peak portions and valley portions. In addition, in the first elastic pad, the above peak portion has a concave portion with a depth smaller than the height of the peak portion, and the above valley portion has a convex portion with a height smaller than the depth of the valley portion. In the present embodiment, it is preferred that the second elastic pad also has a plurality of peak portions and valley portions formed by bending, the above peak portion has a concave portion with a depth smaller than the height of the peak portion, and the above valley portion has a convex portion with a height smaller than the depth of the valley portion.
[0064] In Figure 1 the example shown, the elastic pad 1 has the following structure: a peak portion 2 is provided at the left end, a valley portion 3 is formed adjacent to it, and the peak portion 2 is further adjacent, and such a structure continues until the valley portion 3 at the right end is reached. Figure 1 In the example shown, three concave portions 4 are formed at three places on the peak portion 2 at the left end of the elastic pad 1, and three convex portions 5 are also formed at three places on the valley portion 3 at the right end. Although the reference numerals are omitted in Figure 1 other peak portions 2 also have three concave portions formed respectively, and other valley portions 3 also have three convex portions formed respectively.
[0065] The number of peaks, valleys, concave and convex parts in the elastic pad is not particularly limited and can be set appropriately. When applied to an electrolytic cell, from the perspective of imparting a more appropriate common surface pressure, the spacing of the peaks and valleys in the elastic pad in a direction perpendicular to the formation direction (i.e., the distance between the vertices of adjacent peaks or valleys) is preferably 3 to 15 mm, more preferably 5 to 11 mm, and the spacing of the concave and convex in a direction perpendicular to the groove is preferably 3 to 15 mm, more preferably 5 to 11 mm.
[0066] It should be noted that, for the sake of convenience, Figure 1 The lines shown in a grid shape in the figure represent the wires constituting the elastic pad, but are not limited to wires of such a structure. As described above, it is preferred to form the above-mentioned peaks, valleys, concave portions and convex portions in a cushion pad having a structure formed by knitting and weaving wires.
[0067] exist Figure 1 In the example shown, the peak 2 at the left end extends along the peak formation direction α, and the height of the peak is substantially constant except for three concave portions 4 in the peak formation direction α. In addition, the valley 3 at the right end extends along the valley formation direction β, and the height of the valley is substantially constant except for three convex portions 5 in the valley formation direction β. Figure 1 In the embodiment, the formation directions of the plurality of peaks and valleys are substantially parallel, but elastic pads whose formation directions are not substantially parallel are also included in the present embodiment, so that a uniform normal surface pressure can be obtained.
[0068] Figure 2 It is shown in Figure 1 A schematic partial cross-sectional view of the elastic pad 1 near the center of the XX' section. Figure 2 The dotted line XX' in FIG. 1 is a line perpendicular to the center of the thickness direction of the elastic pad 1. The shape represented by Y corresponds to a peak portion formed with a concave portion and a valley portion formed with a convex portion. Figure 2 The shape represented by Z corresponds to the peak portion where no concave portion is formed and the valley portion where no convex portion is formed. Figure 2 The middle is at the rear.
[0069] The height h1 represented by the vertical line from the dotted line XX' to the highest point of the peak without the concave portion corresponds to the "height of the peak". In addition, the height h2 represented by the distance from the highest point of the peak to the lowest point of the concave portion corresponds to the "depth of the concave portion". Figure 2 As shown, in the elastic pad of this embodiment, the relationship of h1>h2 holds.
[0070] In addition, the height h3 represented by the vertical line from the dotted line XX' to the lowest point of the valley where the convex portion is not formed corresponds to the "depth of the valley". In addition, the height h4 represented by the distance from the lowest point of the valley to the highest point of the convex portion corresponds to the "height of the concave portion". Figure 2 As shown, in the elastic pad of this embodiment, the relationship h3>h4 holds.
[0071] By making the relationship between the peaks, valleys, recesses, and protrusions satisfy the above relationship, when the elastic pad of the present embodiment is applied to an electrolytic cell, an appropriate normal surface pressure can be applied to prevent damage to the ion exchange membrane.
[0072] From the same aspects as above, the value of h1 is preferably 1.8 to 3.0 mm, more preferably 2.0 to 2.8, the value of h2 is preferably 0.6 to 2.2 mm, more preferably 0.8 to 2.0 mm, the value of h3 is preferably 1.8 to 3.0 mm, more preferably 2.0 to 2.8, and the value of h4 is preferably 0.6 to 2.2 mm, more preferably 0.8 to 2.0 mm.
[0073] In this embodiment, the peaks and valleys are preferably provided with a herringbone pattern in the surface direction of the elastic pad. Figure 3 As shown, the herringbone pattern has an inflection point 6 where the pattern is changed by an angle θ formed by a formation direction γ of one peak and a formation direction γ' of another peak. Thus, it is preferred that the inflection point in the herringbone pattern is 1 point, and the angle at the inflection point is greater than 90°. In this embodiment, if the shapes of the peaks, valleys, concave portions, and convex portions are more uniform, there is a tendency to obtain more uniform rebound characteristics. From this aspect, it is preferred to adjust the shape of the elastic pad. Although not limited to this, it is known that the number of inflection points and the size of the corners will also affect the rebound characteristics. For example, from the above-mentioned aspect, the number of inflection points can be 1, and the angle θ can be greater than 90°, preferably 130 to 160°.
[0074] The thickness of the elastic pad of the present embodiment is not particularly limited, and can be appropriately set in consideration of the distance between the anode in the desired electrolytic cell and the collector disposed in the cathode chamber, the flexibility of the elastic pad, etc. In the case of a typical electrolytic cell, the thickness of the elastic pad of the present embodiment can be, for example, about 0.5 mm to 20 mm, preferably 3 mm to 15 mm, and more preferably 4 mm to 10 mm. The thickness of the elastic pad of the present embodiment can be measured, for example, using a tensile compression tester (trade name SDT-201NA-SH) manufactured by Imada Manufacturing Co., Ltd., and more specifically, can be measured by the method described in the examples described later.
[0075] The softness of the elastic pad of the present embodiment is not particularly limited, and for example, an elastic pad having a surface pressure in the range of 2kPa to 40kPa generated during normal use can be used. When the surface pressure generated during normal use is 2kPa or more, there is a tendency that the pressing pressure on the ion exchange membrane is sufficiently increased, and when the surface pressure is 40kPa or less, there is a tendency that the pressing pressure on the ion exchange membrane can be prevented from becoming too large. From the same aspect, it is preferred to use an elastic pad having a surface pressure in the range of 13kPa to 34kPa generated during normal use.
[0076] The elastic pad of this embodiment can also be used by being folded at any position, or can be used without being folded, or can be used by overlapping multiple sheets. It should be noted that, as described above, the elastic pad of this embodiment is not simply a shape having peaks and valleys, but is constructed in a manner that the peaks have concave portions and the valleys have convex portions, so that while improving the resistance to adverse pressure differences, the common surface pressure can also be appropriately reduced. Therefore, even if the elastic pad of this embodiment is not used in multiple overlapping sheets (even when only one sheet is used), it is possible to maintain a zero-spacing structure and prevent membrane damage.
[0077] In the present embodiment, when electrolysis is performed, the elastic pad is preferably installed on the current collector as described above. There is no particular limitation on the installation method, and for example, a method of fixing by spot welding, a method of fixing by a pin made of resin or a wire made of metal, etc. can be cited. On the other hand, from the aspect of the ease of installation in the electrolytic cell and the aspect of preventing the disconnection of the wire material that can constitute the elastic pad, it is preferred to use the elastic pad in a state where the four sides are folded into the current collector, respectively, compared with the above-mentioned fixing method.
[0078] In the second elastic pad, the repulsion force of the elastic pad measured when pressed in such a way that the thickness of the elastic pad becomes 2 mm (hereinafter also referred to as "parameter (i)") is 5 kPa to 30 kPa, and the thickness of the elastic pad when the pressure is released after being compressed at a pressure of 40 kPa for 20 seconds (hereinafter also referred to as "parameter (ii)") is 1 mm or more. In the second elastic pad, since parameter (i) is 5 kPa or more, sufficient pressure can be used to make the electrode contact with the ion exchange membrane, so the electrolysis performance is excellent; since parameter (i) is 30 kPa or less, moderate pressure can be applied, so the pressure on the ion exchange membrane is not too strong, and the performance of preventing damage to the ion exchange membrane is excellent. From this aspect, in the second elastic pad, parameter (i) is preferably 7 kPa to 28 kPa, and more preferably 9 kPa to 27 kPa.
[0079] In addition, in the second elastic pad, since the parameter (ii) is 1 mm or more, the electrolytic performance is excellent. From this point of view, the parameter (ii) is preferably 1.2 mm or more, more preferably 1.5 mm or more, and even more preferably 2.0 mm or more.
[0080] Parameters (i) and (ii) can be measured by the method described in the following examples. In addition, these parameters can be adjusted to the above ranges by, for example, making the repulsive force in the surface direction of the elastic pad have a gradient. An example of such an adjustment method is described below.
[0081] [Method for manufacturing elastic pad]
[0082] The method for producing the elastic pad according to the present embodiment is not particularly limited, and may include the following steps.
[0083] First, an elastic pad precursor having a desired shape is manufactured using a conductive elastic member.
[0084] Next, a mold having shapes corresponding to the peaks, valleys, recesses, and protrusions described above is prepared, and the elastic pad precursor is given a desired shape using the mold.
[0085] In addition to the above method, the elastic pad of the present embodiment can also be produced by applying a gear roller with an appropriately adjusted tooth tip distance to an elastic pad precursor.
[0086] As described above, the elastic pad is required to be able to maintain its shape to a degree that can maintain zero spacing even when subjected to a certain degree of adverse pressure difference (adverse pressure difference resistance), and it is also required that the common surface pressure is not too high. In the case of a strong elastic pad made in order to improve the adverse pressure difference resistance, the common surface pressure tends to increase, and the possibility of causing membrane damage increases. On the other hand, in the case of a soft elastic pad made in order to reduce the common surface pressure, the adverse pressure difference resistance tends to decrease, and it is difficult to maintain zero spacing. In this way, there is a trade-off relationship between maintaining the zero spacing structure and preventing membrane damage. That is, it can be said that in the prior art, there is a trade-off relationship between making parameter (i) within an appropriate range and making parameter (ii) within an appropriate range. The second elastic pad can solve such a problem of the prior art. For example, an elastic pad belonging to the second elastic pad and not belonging to the first elastic pad can be manufactured as follows.
[0087] First, an elastic pad (not belonging to the first elastic pad) of a desired size is prepared and divided into, for example, three or more regions. Next, at least one region is subjected to compression treatment to reduce the thickness and the normal surface pressure, thereby manufacturing a second elastic pad. There is no particular limitation on the arrangement of the regions where the compression treatment has been applied and the regions where the compression treatment has not been applied. For example, it is preferred to alternately arrange the regions where the compression treatment has not been applied, the regions where the compression treatment has been applied, and the regions where the compression treatment has not been applied (see Example 7 described later; see Example 7). Fig.11 ), or the compressed area, the area not compressed, and the compressed area are arranged alternately in the order of (Example 8 described later; see Example 8 of the embodiment ... Fig.12 ).
[0088] In addition, the method of manufacturing the second elastic pad and not the first elastic pad is not limited to the above example, and the pad may be manufactured as follows, for example.
[0089] First, prepare an elastic pad (not belonging to the first elastic pad) of the desired size, and prepare a sample divided into, for example, three or more regions. Then, at least one of the samples is subjected to compression treatment to reduce the thickness and reduce the common surface pressure. In addition, for example, the second elastic pad having a region where compression treatment has been implemented and a region where compression treatment has not been implemented can be manufactured by integrating the side of the sample where compression treatment has been implemented and the sample where compression treatment has not been implemented (the side that is not in contact with the electrode or the collector when the electrolytic cell is running). There is no particular limitation on integration here, for example, the wires in each sample can be integrated by winding or welding them together, or they can be integrated using a conductive adhesive. There is no particular limitation on the configuration of the sample where compression treatment has been implemented and the sample where compression treatment has not been implemented. For example, it is preferred to alternately configure in the order of the region where compression treatment has not been implemented, the region where compression treatment has been implemented, and the region where compression treatment has not been implemented, or alternately configure in the order of the region where compression treatment has been implemented, the region where compression treatment has not been implemented, and the region where compression treatment has been implemented.
[0090] It should be noted that, in the elastic pad obtained in the manner of the above example, the value of parameter (i) can be controlled by, for example, adjusting the area ratio of the area where the compression treatment has been implemented to the area where the compression treatment has not been implemented. For example, by increasing the area ratio S1 / S2 of the total area S1 of the area where the compression treatment has been implemented to the total area S2 of the area where the compression treatment has not been implemented, parameter (i) tends to decrease, and in this case, parameter (ii) tends to hardly change. The value of parameter (ii) can be adjusted to the above range by using, for example, nickel, iron, cobalt, molybdenum, lead, or alloys thereof as the metal material constituting the elastic pad, or by adjusting the wire diameter of the wire composed of these metal materials to, for example, about 0.05 mm to 0.25 mm.
[0091] [Electrolyzer]
[0092] The electrolytic cell of the present embodiment comprises an anode chamber including an anode, a cathode chamber including an elastic pad of the present embodiment, a current collector and a cathode, and an ion exchange membrane disposed between the anode chamber and the cathode chamber, wherein the elastic pad is disposed between the current collector and the cathode in the cathode chamber, and the elastic pad applies pressure to the cathode in a direction toward the ion exchange membrane. The electrolytic cell of such a structure can prevent damage to the ion exchange membrane and operate stably. In the present embodiment, the combination of the anode chamber and the cathode chamber is referred to as an electrolytic cell, which is described in detail below.
[0093] (Electrolytic Cell)
[0094] Figure 4 An example of an electrolytic cell constituting the electrolytic tank of the present embodiment is shown in the form of a cross-sectional schematic diagram. The electrolytic cell 100 includes: an anode chamber 10; a cathode chamber 20; a partition wall 30 separating the anode chamber 10 and the cathode chamber 20; an anode 11 disposed in the anode chamber 10; and a cathode 21 disposed in the cathode chamber 20. The anode 11 and the cathode 21 belonging to one electrolytic cell 100 are electrically connected to each other.
[0095] In addition, the cathode chamber 20 further has a cathode 21, a current collector 23, a support 24 supporting the current collector, and an elastic pad 1 arranged in the cathode chamber 20. The elastic pad 1 is arranged between the current collector 23 and the cathode 21. The support 24 is arranged between the current collector 23 and the partition wall 30. The current collector 23 is electrically connected to the cathode 21 via the elastic pad 1. The partition wall 30 is electrically connected to the current collector 23 via the support 24. Therefore, the partition wall 30, the support 24, the current collector 23, the elastic pad 1 and the cathode 21 are electrically connected. The cathode 21 and the reverse current absorber can be directly connected or indirectly connected via the current collector, the support, the metal elastic body or the partition wall. Preferably, the entire surface of the cathode 21 is coated with a catalyst layer used for the reduction reaction. In addition, regarding the form of electrical connection, the partition wall 30 and the support 24, the support 24 and the collector 23, and the collector 23 and the elastic pad 1 may be directly attached, respectively, and the cathode 21 may be stacked on the elastic pad 1. Examples of methods for directly attaching these components to each other include welding and the above-mentioned folding.
[0096] By providing the elastic pad 1 between the current collector 23 and the cathode 21, each cathode 21 of the plurality of electrolytic cells 100 connected in series is pressed against the ion exchange membrane 2, and the distance between each anode 11 and each cathode 21 is shortened, so that the voltage applied to the plurality of electrolytic cells 100 connected in series as a whole can be reduced. By reducing the voltage, the power consumption can be reduced. As described above, the elastic pad of the present embodiment can apply pressure to the ion exchange membrane with a moderate normal pressure surface pressure, so that a zero-spacing structure can be adopted while maintaining the current efficiency, and it is also preferable to prevent damage to the ion exchange membrane.
[0097] It should be noted that the cathode can be directly overlapped on the elastic pad, or it can be a structure in which the cathode is overlapped through other conductive components. As a cathode that can be used in zero spacing, a cathode with a thin wire diameter and a small mesh number is also highly flexible and is preferred. There is no particular limitation on the wire material constituting such a cathode, but a cathode with a wire diameter of 0.1 to 0.5 mm and a mesh size of 20 to 80 meshes can also be used.
[0098] Figure 5 It is a cross-sectional view of two adjacent electrolytic cells 100 in the electrolytic tank 4 of the present embodiment. Figure 6 An electrolytic cell 400 is shown. Figure 7 FIG. 4 shows the assembly process of the electrolytic cell 400. Figure 5 As shown, the electrolytic cell 100, the ion exchange membrane 2, and the electrolytic cell 100 are arranged in series. In the two adjacent electrolytic cells in the electrolytic cell, the ion exchange membrane 2 is arranged between the anode chamber of one electrolytic cell 100 and the cathode chamber of the other electrolytic cell 100. That is, the anode chamber 10 of the electrolytic cell 100 and the cathode chamber 20 of the adjacent electrolytic cell 100 are separated by the ion exchange membrane 2. Figure 6 As shown, the electrolytic cell 400 is composed of a plurality of electrolytic cells 100 connected in series via an ion exchange membrane 2. That is, the electrolytic cell 400 is a bipolar electrolytic cell having a plurality of electrolytic cells 100 arranged in series and an ion exchange membrane 2 arranged between adjacent electrolytic cells 100. Figure 7 As shown, the electrolytic tank 400 is assembled by arranging a plurality of electrolytic cells 100 in series via an ion exchange membrane 2 and connecting them using a pressurizer 500 .
[0099] The electrolytic cell 400 has an anode terminal 700 and a cathode terminal 600 connected to a power source. Among the multiple electrolytic cells 100 connected in series in the electrolytic cell 400, the anode 11 of the electrolytic cell 100 at the end is electrically connected to the anode terminal 700. Among the multiple electrolytic cells 2 connected in series in the electrolytic cell 400, the cathode 21 of the electrolytic cell at the end on the opposite side of the anode terminal 700 is electrically connected to the cathode terminal 600. The current during electrolysis flows from the anode terminal 700 side through the anode and cathode of each electrolytic cell 100 toward the cathode terminal 600. It should be noted that an electrolytic cell (anode terminal cell) having only an anode chamber and an electrolytic cell (cathode terminal cell) having only a cathode chamber can be configured at both ends of the connected electrolytic cell 100. In this case, the anode terminal cell configured at one end is connected to the anode terminal 700, and the cathode terminal cell configured at the other end is connected to the cathode terminal 600.
[0100] In the case of electrolysis of salt water, salt water is supplied to each anode chamber 10, and pure water or a low-concentration sodium hydroxide aqueous solution is supplied to the cathode chamber 20. Each liquid is supplied to each electrolytic cell 100 via an electrolyte supply hose (omitted in the figure) from an electrolyte supply pipe (omitted in the figure). In addition, the electrolyte and the products brought about by electrolysis are recovered by an electrolyte recovery pipe (omitted in the figure). During electrolysis, sodium ions in the salt water move from the anode chamber 10 of one electrolytic cell 100 to the cathode chamber 20 of the adjacent electrolytic cell 100 through the ion exchange membrane 2. As a result, the current in the electrolysis flows in the direction in which the electrolytic cells 100 are connected in series. That is, the current flows from the anode chamber 10 to the cathode chamber 20 through the ion exchange membrane 2. As the salt water is electrolyzed, chlorine gas is generated on the anode 11 side, and sodium hydroxide (solute) and hydrogen gas are generated on the cathode 21 side.
[0101] (Separation wall)
[0102] The partition wall 30 is sometimes also called a separator, and is disposed between the anode chamber 10 and the cathode chamber 20 to divide the anode chamber 10 and the cathode chamber 20. As the partition wall 30, a known member used as a separator for electrolysis can be used, for example, a partition wall having a plate made of nickel welded on the cathode side and a plate made of titanium welded on the anode side, etc.
[0103] (Anode chamber)
[0104] The anode chamber 10 has an anode 11. In addition, the anode chamber 10 preferably has: an anode-side electrolyte supply unit for supplying electrolyte to the anode chamber 10; a baffle plate disposed above the anode-side electrolyte supply unit and disposed approximately parallel to or obliquely to the partition wall 30; and an anode-side gas-liquid separation unit disposed above the baffle plate and separating gas from the electrolyte mixed with gas.
[0105] (anode)
[0106] An anode 11 is provided in the frame of the anode chamber 10. A metal electrode such as DSA (registered trademark: DeNora Permelec Co., Ltd.) can be used as the anode 11. DSA is a titanium substrate whose surface is coated with oxides containing ruthenium, iridium, and titanium as components.
[0107] In the present embodiment, from the viewpoint of damage to the ion exchange membrane used as the diaphragm, the distance between the anode in the electrolytic cell and the reverse current absorbing member is preferably 35 mm to 0.1 mm.
[0108] (Anode side electrolyte supply unit)
[0109] The anode side electrolyte supply unit is a component that supplies electrolyte to the anode chamber 10, and is connected to the electrolyte supply pipe. The anode side electrolyte supply unit is preferably arranged below the anode chamber 10. As the anode side electrolyte supply unit, for example, a tube (dispersion tube) having an opening formed on the surface can be used. The tube is more preferably arranged parallel to the bottom 19 of the electrolytic cell along the surface of the anode 11. The tube is connected to an electrolyte supply pipe (liquid supply nozzle) that supplies electrolyte to the electrolytic cell 100. The electrolyte supplied by the liquid supply nozzle is transported to the electrolytic cell 100 through the tube, and is supplied to the inside of the anode chamber 10 from the opening provided on the surface of the tube. By arranging the tube parallel to the bottom 19 of the electrolytic cell along the surface of the anode 11, the electrolyte can be uniformly supplied to the inside of the anode chamber 10, which is preferred.
[0110] (Gas-liquid separation section on the anode side)
[0111] The anode-side gas-liquid separator is preferably disposed above the baffle. In electrolysis, the anode-side gas-liquid separator has the function of separating generated gases such as chlorine from the electrolyte. It should be noted that, unless otherwise specified, the above refers to Figure 4 The upper direction of the electrolytic cell 100 is Figure 4 The electrolytic cell 100 is in the downward direction.
[0112] During electrolysis, if the generated gas produced in the electrolytic cell 100 becomes a mixed phase (gas-liquid mixed phase) with the electrolyte and is discharged outside the system, vibration will be generated due to the pressure change inside the electrolytic cell 100, which may cause physical damage to the ion exchange membrane. In order to suppress this situation, the electrolytic cell 100 of this embodiment is preferably provided with an anode side gas-liquid separation unit for separating gas from liquid. Preferably, a defoaming plate for calibrating bubbles is provided in the anode side gas-liquid separation unit. When the gas-liquid mixed phase flow passes through the defoaming plate, the bubbles burst, thereby being able to be separated into electrolyte and gas. As a result, vibration during electrolysis can be prevented.
[0113] (Baffle)
[0114] The baffle is preferably arranged above the electrolyte supply part on the anode side and arranged approximately parallel to or obliquely to the partition wall 30. The baffle is a partition that controls the flow of the electrolyte in the anode chamber 10. By setting the baffle, the electrolyte (brine, etc.) can be circulated internally in the anode chamber 10, and its concentration can be made uniform. In order to cause internal circulation, the baffle is preferably arranged in a manner that separates the space near the anode 11 from the space near the partition wall 30. From this aspect, the baffle is preferably arranged in a manner opposite to each surface of the anode 11 and the partition wall 30. By performing electrolysis in the space near the anode separated by the baffle, the electrolyte concentration (brine concentration) is reduced, and chlorine and other generated gases are generated. As a result, a gas-liquid specific gravity difference is generated between the space near the anode 11 separated by the baffle and the space near the partition wall 30. Utilizing this specific gravity difference, the internal circulation of the electrolyte in the anode chamber 10 can be promoted, and the concentration distribution of the electrolyte in the anode chamber 10 can be made more uniform.
[0115] It should be noted that although Figure 4 Although not shown, a current collector may be separately provided inside the anode chamber 10. The current collector may be made of the same material and structure as the current collector of the cathode chamber described later. In addition, in the anode chamber 10, the anode 11 itself may also function as a current collector.
[0116] (Cathode chamber)
[0117] The cathode chamber 20 has a cathode 21 and a reverse current absorber, and the cathode 21 is electrically connected to the reverse current absorber. In addition, the cathode chamber 20 also preferably has a cathode side electrolyte supply unit, a cathode side gas-liquid separation unit, and a baffle, similar to the anode chamber 10. It should be noted that among the various parts constituting the cathode chamber 20, the description of the parts that are the same as the various parts constituting the anode chamber 10 is omitted.
[0118] (Current Collector)
[0119] The cathode chamber 20 preferably includes a current collector 23. This can improve the current collection effect. Figure 4In the example shown, the collector 23 is plate-shaped, and in this embodiment, it is preferably arranged so that the surface of the collector is substantially parallel to the surface of the cathode 21. Such a collector tends to suppress the deflection of the metal elastic body described later and obtain a current collecting effect.
[0120] The current collector 23 is preferably made of a metal having electrical conductivity, such as nickel, iron, copper, silver, titanium, etc. The current collector 23 may be a mixture, alloy, or composite oxide of these metals. It should be noted that the shape of the current collector 23 may be any shape as long as it can function as a current collector, and may also be a mesh shape.
[0121] (Support)
[0122] The cathode chamber 20 preferably includes a support 24 that electrically connects the current collector 23 and the partition wall 30. This allows the current to flow efficiently.
[0123] The support 24 is preferably made of an electrically conductive metal such as nickel, iron, copper, silver, or titanium. The support 24 may be in any shape as long as it can support the collector 23, and may be in the shape of a rod, a plate, or a mesh. Figure 4 In the embodiment shown, the support 24 is plate-shaped, preferably having a structure in which a metal plate is bent into an L-shape. A plurality of support bodies 24 are arranged between the partition wall 30 and the current collector 23. A plurality of support bodies 24 are arranged in such a manner that each surface is parallel to each other. The support body 24 is arranged substantially perpendicularly to the partition wall 30 and the current collector 23.
[0124] (Baffle)
[0125] The baffle is preferably arranged above the cathode side electrolyte supply part and arranged approximately parallel to or obliquely to the partition wall 30. The baffle is a partition that controls the flow of the electrolyte in the cathode chamber 20. By setting the baffle, the electrolyte (brine, etc.) can be circulated internally in the cathode chamber 20, and its concentration can be made uniform. In order to cause internal circulation, the baffle is preferably arranged in a manner that separates the space near the cathode 21 from the space near the partition wall 30. From this aspect, the baffle is preferably arranged in a manner opposite to each surface of the cathode 21 and the partition wall 30. By performing electrolysis in the space near the cathode separated by the baffle, the electrolyte concentration (brine concentration) is reduced, and hydrogen and other generated gases are generated. As a result, a gas-liquid specific gravity difference is generated between the space near the cathode 21 separated by the baffle and the space near the partition wall 30. Utilizing this specific gravity difference, the internal circulation of the electrolyte in the cathode chamber 20 can be promoted, and the concentration distribution of the electrolyte in the cathode chamber 20 can be made more uniform.
[0126] (Anode side gasket, cathode side gasket)
[0127] The anode side gasket 51 is preferably arranged on the surface of the frame constituting the anode chamber 10. The cathode side gasket 50 is preferably arranged on the surface of the frame constituting the cathode chamber 20. The anode side gasket 51 of one electrolytic cell and the cathode side gasket 50 of the adjacent electrolytic cell are connected to each other in a manner of sandwiching the ion exchange membrane 2 (see Figure 6 ). By using these gaskets, when a plurality of electrolytic cells 100 are connected in series via the ion exchange membrane 2, airtightness can be imparted to the connection points.
[0128] The sealing gasket seals the ion exchange membrane and the electrolytic cell. As a specific example of the sealing gasket, a frame-shaped rubber sheet with an opening formed in the center can be cited. Regarding the sealing gasket, it is required to be resistant to corrosive electrolytes or generated gases, and can be used for a long time. Therefore, from the aspects of chemical resistance and hardness, ethylene propylene diene monomer rubber (EPDM rubber) and diethylene propylene diene monomer rubber (EPM rubber) are usually used as sealing gaskets. In addition, as required, a sealing gasket formed by coating the area (liquid contact part) in contact with the liquid with a fluorine resin such as polytetrafluoroethylene (PTFE) or tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA) can also be used. These sealing gaskets have openings respectively in a manner that does not hinder the flow of the electrolyte, and their shapes are not particularly limited. For example, a frame-shaped sealing gasket can be pasted with an adhesive or the like along the periphery of each opening of the anode chamber frame constituting the anode chamber 10 or the cathode chamber frame constituting the cathode chamber 20. Furthermore, for example, when two electrolytic cells 100 are connected via the ion exchange membrane 2 (see Figure 6 ), as long as each electrolytic cell 100 to which the sealing gasket is attached can be fastened via the ion exchange membrane 2. Thus, leakage of the electrolyte, alkali metal hydroxide generated by electrolysis, chlorine gas, hydrogen gas, etc. to the outside of the electrolytic cell 100 can be suppressed.
[0129] (Ion Exchange Membrane)
[0130] The ion exchange membrane 2 is not particularly limited, and known ion exchange membranes can be used. For example, in the case of manufacturing chlorine and alkali by electrolysis of alkali metal chlorides, fluorine-containing ion exchange membranes are preferred from the aspects of excellent heat resistance and chemical resistance. As fluorine-containing ion exchange membranes, fluorine-containing ion exchange membranes having the function of selectively permeating ions generated during electrolysis and containing fluorine-containing polymers with ion exchange groups can be cited. The fluorine-containing polymers with ion exchange groups mentioned here refer to fluorine-containing polymers having ion exchange groups or ion exchange group precursors that can be hydrolyzed to become ion exchange groups. As such fluorine-containing polymers, for example, polymers composed of the main chain of fluorinated hydrocarbons, having functional groups that can be converted into ion exchange groups by hydrolysis, etc. as pendant side chains, and melt-processable polymers can be cited.
[0131] Example
[0132] The present embodiment is described in detail below by way of examples. It should be noted that the present embodiment is not limited to the following examples.
[0133] [Example 1]
[0134] (Manufacture of elastic pads)
[0135] As a conductive material, Ni wire with a wire diameter of 0.17 mm was knitted to obtain an elastic mat precursor 1 composed of a woven fabric with a mesh size of 1.5×2.5 mm. The elastic mat precursor was patterned using a herringbone gear roll (gear roll 1) with a torsion angle θ of 15° (angle 150°) to obtain an elastic mat precursor 2. Peaks and valleys were formed by this operation, and the thickness of the elastic mat precursor 2 was 4.7 mm.
[0136] Next, a gear roller (gear roller 2) similar to gear roller 1 was prepared except that the distance between the tooth tops was different, and a concave portion was formed in the peak portion with a height difference of 1.1 mm, and a convex portion was formed in the valley portion with a height difference of 1.1 mm in the elastic pad precursor 2, thereby obtaining an elastic pad (1.2 m×2.4 m) of Example 1. At this time, the gear roller 2 was used in a manner that the pattern obtained by inverting the herringbone pattern transferred by the gear roller 1 was further transferred to the elastic pad precursor 2.
[0137] Regarding the height of the peaks, the depth of the concave portions, the depth of the valley portions, and the height of the convex portions of the obtained elastic pad, as shown in FIG. Figure 8 As shown in (a), a measuring rod with a certain thickness is placed on multiple elastic pads, such as Figure 8 As shown in (b), each dimension is measured by obtaining it using the imaginary upper surface L3 and imaginary lower surface L2 formed by the mounting surface L1 of the elastic pad and the plurality of rods.
[0138] The thickness of the elastic pad precursor and the elastic pad were measured using a measuring table equipped with a fixed measuring table and a measuring plate (100 mm square; area 10,000 mm 2 ) was measured using a tension-compression testing machine (manufactured by Imada Manufacturing Co., Ltd.; trade name: SDT-201NA-SH) as follows.
[0139] First, in a state where nothing is placed on the measuring table of the tensile compression tester, the measuring plate is lowered to make contact, and the position of the measuring plate at this time is taken as the height 0. Then, the measuring plate is raised, and the elastic pad precursor or the elastic pad is placed on the measuring table of the tensile compression tester, and the measuring plate is lowered again. After making contact with the elastic pad precursor or the elastic pad, the position of the measuring plate is adjusted in such a way that the rebound force is converted into 0.1 kPa in terms of surface pressure. The height of the measuring plate at this time is taken as the thickness of the elastic pad precursor or the elastic pad. The thickness (initial thickness) is also measured in the same way in the following examples and comparative examples.
[0140] (Manufacture of electrolytic cells)
[0141] A zero-gap electrolytic cell with a width of 2400 mm and a height of 1289 mm is prepared as follows. A nickel plate with holes having a size of 1149 mm × 2347 mm and a thickness of 1.2 mm is prepared as a current collector, and the above-mentioned elastic pad is arranged on its surface. Next, a rotating circular plate with a diameter of 100 mm is used to bend the peripheral portion (all 4 sides) of the elastic pad in a manner such that it is located on the back side of the current collector through the gap formed between the frame of the electrolytic cell and the edge of the current collector, and a scraper is used to press it onto the back side of the current collector across the edge of the current collector. The folded-in length at this time is 10 mm.
[0142] Furthermore, a cathode formed by coating ruthenium oxide on a nickel fine mesh substrate is arranged on an elastic pad. Fig. 9 As shown, the peripheral portion (all four sides) of the cathode is bent using a rotating circular plate with a diameter of 100 mm. That is, the elastic pad 1 and the upper end of the cathode 21 are inserted into the gap S formed between the frame 34 and the edge 40c of the collector 40, and fixed in a manner of being folded over the edge 40c of the collector 40 to the back side 40b. The folded length L at this time is 10 mm.
[0143] (Electrolysis Evaluation)
[0144] The electrolytic cell was assembled into an electrolytic cell, an anode formed by coating the surface of a titanium substrate with oxides containing ruthenium and iridium as components was used as an anode, ACIPLEX (registered trademark) F6801 was used as an ion exchange membrane, about 300 g / L of brine was supplied as an anode liquid, dilute sodium hydroxide was supplied to the cathode chamber in such a manner that the sodium hydroxide concentration near the discharge port was about 32 wt %, and the electrolysis temperature was 80 to 90° C., the gas pressure on the anode chamber side was 40 kPa, the gas pressure on the cathode chamber side was 44 kPa, and the current density was 4 kA / m 2 The electrolysis was carried out for 5 days under the conditions, after which the current density was increased to 7 kA / m 2 , and electrolysis was performed for a total of 28 days. It should be noted that in the above electrolysis, hydrochloric acid was added to the supplied brine in such a way that the pH of the brine near the discharge port of the anolyte was 2. The ion exchange membrane removed after electrolysis was visually observed, and no abnormality was observed in appearance. The surface coating of the ion exchange membrane was then removed and observed, and only 55 slight carboxylic acid layer damages were produced (recorded as "membrane damage" in the table), which was in a good state to the extent that it would not affect the electrolysis performance.
[0145] [Comparative Example 1]
[0146] An elastic mat of Comparative Example 1 was obtained in the same manner as in Example 1 except that the gear roll 2 was not used. The elastic mat was subjected to the same electrolysis evaluation as in Example 1. The results are shown in Table 1. The release thickness after 40 kPa pressure application was sufficient, but the surface pressure at 2 mm was excessive, so the membrane was often damaged.
[0147] (Surface pressure)
[0148] The elastic pads obtained in Example 1 and Comparative Example 1 were used as subjects, and the contact surface pressure relative to the thickness of the elastic pads was measured using a tension-compression tester (trade name SDT-201NA-SH) manufactured by Imada Manufacturing Co., Ltd. as follows.
[0149] First, the initial thickness of the elastic pad obtained in Example 1 and Comparative Example 1 was measured. Then, the measuring plate was lowered and contacted with the elastic pad. The position of the measuring plate was adjusted so as to achieve a predetermined repulsive force and pressed. The pressure and thickness at this time were recorded. The repulsive force value was changed each time the pressing was repeated, and the contact surface pressure was plotted against the thickness of the elastic pad. The results are shown in FIG. Fig.10It should be noted that the value of the rebound force (converted into surface pressure) is set to 1.5 kPa at the time of the initial pressing, and the rebound force is changed in the order of 3.0 kPa, 5.0 kPa, 7.0 kPa, 9.0 kPa, 11.0 kPa, 13.0 kPa, 16.0 kPa, 19.0 kPa, 22.0 kPa, 25.0 kPa, 28.0 kPa, 31.0 kPa, 34.0 kPa, 37.0 kPa, 40.0 kPa and 43.0 kPa in the subsequent pressing.
[0150] In a zero-gap electrolyzer, the thickness of the elastic pad (consistent with the gap between the collector and the cathode when the electrolyzer is in operation) is approximately 2 to 3 mm, but according to Fig.10 It can be seen that, within this range, the surface pressure of the elastic pad of Example 1 is significantly reduced compared to Comparative Example 1.
[0151] It should be noted that the surface pressure when the thickness of the elastic pad was 2 mm was 23 kPa in Example 1 and was 41 kPa in Comparative Example 1.
[0152] (Released thickness after 40kPa pressurization)
[0153] The obtained elastic pad was used as an object, and the contact surface pressure relative to the thickness of the elastic pad was measured as follows using the same tension and compression tester as described above (manufactured by Imada Seisakusho Co., Ltd.; trade name SDT-201NA-SH). That is, a 100 mm × 100 mm (area 10,000 mm 2 ) is brought into contact with the center of an elastic pad cut to 120 mm × 120 mm (the elastic pad on which the above-mentioned "surface pressure" measurement is not performed), and is pressed until the rebound force is displayed as 40 kPa when converted to surface pressure. After holding for 20 seconds, the measuring plate is retracted upward until the rebound force is displayed as 0.1 kPa, and the thickness at this time is taken as the thickness when released.
[0154] [Example 2]
[0155] An elastic mat of Example 2 was obtained in the same manner as in Example 1 except that the distance between the tooth tips of the gear roller 2 was changed. This elastic mat was subjected to the same electrolysis evaluation as in Example 1. The results are shown in Table 1.
[0156] [Example 3]
[0157] An elastic mat of Example 3 was obtained in the same manner as in Example 1 except that the distance between the tooth tips of the gear roller 2 was changed. This elastic mat was subjected to the same electrolysis evaluation as in Example 1. The results are shown in Table 1.
[0158] [Example 4]
[0159] An elastic mat of Example 4 was obtained in the same manner as in Example 1 except that the distance between the tooth tips of the gear roller 2 was changed. This elastic mat was subjected to the same electrolysis evaluation as in Example 1. The results are shown in Table 1.
[0160] [Example 5]
[0161] An elastic mat of Example 5 was obtained in the same manner as in Example 1 except that the distance between the tooth tips of the gear roller 2 was changed. This elastic mat was subjected to the same electrolysis evaluation as in Example 1. The results are shown in Table 1.
[0162] [Example 6]
[0163] An elastic mat of Example 6 was obtained in the same manner as in Example 2 except that the conductive material was changed to a Ni wire having a wire diameter of 0.15 mm. The elastic mat was subjected to the same electrolytic evaluation as in Example 2. The results are shown in Table 1.
[0164] [Example 7]
[0165] The elastic pad of Comparative Example 1 was cut into a size of 120 mm in length and 120 mm in width. Fig.11 The sample A was divided into three regions as shown in the figure, and only the central region of 120 mm in length and 33 mm in width was subjected to compression treatment so as to achieve a thickness of 1.6 mm, and the obtained sample A was used as the elastic pad of Example 7 (for evaluation of surface pressure and release thickness after 40 kPa pressurization). The sample A had a 33% compressed region and a 67% uncompressed region based on area.
[0166] In the compression treatment, the cut elastic mat was placed on a PVC plate having a sufficient thickness and subjected to compression treatment using a 120 mm×33 mm pressing plate (made of SUS) using a tension-compression tester.
[0167] Next, the elastic pad of Comparative Example 1 was subjected to compression without reducing its size, and the obtained sample B was used as the elastic pad of Example 7 (for electrolysis evaluation). It should be noted that the positional relationship and area ratio of the uncompressed area, the compressed area, and the uncompressed area in the sample B were the same as those of the sample A.
[0168] [Example 8]
[0169] The elastic pad of Comparative Example 1 was cut into a size of 120 mm in length and 120 mm in width in the same manner as in Example 7. Fig.12The sample C was divided into three regions as shown in the figure, and the regions of length 120 mm×width 43.5 mm at both ends were subjected to compression treatment in a manner to achieve a thickness of 1.6 mm, and the obtained sample C was used as the elastic pad of Example 8 (for evaluation of surface pressure and release thickness after 40 kPa pressurization). The sample C had a 67% compressed region and a 33% uncompressed region based on area.
[0170] In the compression treatment, the cut elastic mat was placed on a PVC plate having sufficient thickness and compressed using a tension-compression tester with two 120 mm x 45 mm pressing plates (made of SUS) placed at both ends of the elastic mat.
[0171] Next, the elastic pad of Comparative Example 1 was subjected to compression without reducing its size, and the obtained sample D was used as the elastic pad of Example 8 (for electrolysis evaluation). It should be noted that the positional relationship and area ratio of the compressed region, the uncompressed region, and the compressed region in the sample D were the same as those of the sample C.
[0172] In Examples 2 to 8, the surface pressure and the released thickness after pressurization of 40 kPa were measured in the same manner as in Example 1 and Comparative Example 1. These results are collectively shown in Table 1.
[0173] [Table 1]
[0174]
[0175] As can be seen from Table 1, compared with Comparative Example 1 which does not satisfy the elastic pad element of the present embodiment, Examples 1 to 6 satisfying the first elastic pad element and Examples 7 to 8 satisfying the second elastic pad element, damage to the ion exchange membrane is suppressed.
[0176] It should be noted that Examples 7 to 8 are made based on Comparative Example 1, but the portion that was compressed in advance is integrated with the portion that was not compressed in advance to form an elastic pad. At this time, the rebound force at a thickness of 2 mm is measured in the form of average surface pressure. Therefore, the measured value is smaller than that of Comparative Example 1. As a result, compared with Comparative Example 1, the membrane damage can also be reduced.
Claims
1. An elastic pad, which is an elastic pad with conductivity, wherein: The elastic pad has a plurality of peaks and valleys formed by bending, The peak has a recess having a depth smaller than the height of the peak, The valley has a convex portion, the convex portion having a height smaller than a depth of the valley, The spacing between the peaks and valleys in the elastic pad in a direction perpendicular to the forming direction is 3 mm to 15 mm. The height h2 represented by the distance from the highest point of the peak to the lowest point of the recess, that is, the depth of the recess is 1.1 mm to 2.0 mm. The height h4 represented by the distance from the lowest point of the valley to the highest point of the convex portion, that is, the height of the concave portion is 1.1 mm to 2.0 mm. The height of the peak, i.e. h1, is 1.8 mm to 2.3 mm. The depth of the valley, ie, h3, is 1.8 mm to 2.3 mm.
2. The elastic pad according to claim 1, wherein: The pitch of the concavo-convex portions of the elastic pad in a direction perpendicular to the groove is 3 mm to 15 mm.
3. The elastic pad according to claim 1, wherein: The height of the peak is 2.0 mm to 2.3 mm.
4. The elastic pad according to claim 1, wherein: The depth of the valley is 2.0 mm to 2.3 mm.
5. The elastic pad according to claim 1, wherein: The thickness of the elastic pad is 0.5 mm to 20 mm.
6. The elastic pad according to claim 1, wherein: The thickness of the elastic pad is 4 mm to 10 mm.
7. The elastic pad according to claim 1, wherein: The surface pressure generated by the elastic pad in normal use is 2 kPa to 40 kPa.
8. The elastic pad according to claim 1, wherein: The surface pressure generated by the elastic pad in normal use is 13 kPa to 34 kPa.
9. The elastic pad according to claim 1, wherein: The cushion-shaped elastic pad precursor is formed using an aggregate of metal wires formed of nickel, iron, cobalt, molybdenum, lead, or an alloy thereof.
10. The elastic pad according to claim 9, wherein: A plurality of the metal wires are prepared and braided to form an elastic pad precursor in the shape of a cushion pad.
11. The elastic pad according to claim 9, wherein: The wire diameter of the metal wire is 0.05 mm to 0.25 mm.
12. The elastic pad of claim 9, wherein: The wire diameter of the metal wire is 0.15 mm to 0.25 mm.
13. The elastic pad of claim 9, wherein: The wire diameter of the metal wire is 0.16 mm to 0.19 mm.
14. The elastic pad of claim 1, wherein: The formation direction of a peak is approximately parallel to the formation direction of the adjacent peak. The formation direction of one valley portion and the formation direction of the adjacent valley portion are both substantially parallel to each other.
15. The elastic pad of claim 1, wherein: The peaks and valleys provide a herringbone pattern in the surface direction of the elastic pad.
16. The elastic pad of claim 15, wherein: The inflection point in the herringbone pattern is one point, and the angle at the inflection point is greater than 90°.
17. The elastic pad of claim 16, wherein: The turning angle is 130° to 160°.
18. The elastic pad according to claim 1, which is folded at any position.
19. The elastic pad of claim 1, wherein: The elastic mat is used in a state where the four sides are folded into the current collector.
20. An electrolytic cell comprising: an anode chamber containing an anode; A cathode chamber comprising an elastic pad according to any one of claims 1 to 19, a current collector and a cathode; and an ion exchange membrane disposed between the anode chamber and the cathode chamber, In the cathode chamber, the elastic pad is arranged between the current collector and the cathode, The elastic pad applies pressure to the cathode in a direction toward the ion exchange membrane.
21. The elastic pad according to claim 1, which is an elastic pad having electrical conductivity, wherein: The thickness of the elastic pad is greater than 2 mm, (i) the repulsive force of the elastic pad measured when pressed so that the thickness of the elastic pad becomes 2 mm is 5 kPa or more and 30 kPa or less, (ii) The elastic pad is compressed at a pressure of 40 kPa for 20 seconds and then has a thickness of 1 mm or more when the pressure is released.
22. The elastic pad of claim 21, wherein: The elastic pad has a plurality of peaks and valleys formed by bending, The peak has a recess having a depth smaller than the height of the peak, The valley portion has a convex portion having a height smaller than a depth of the valley portion.
23. The resilient pad of claim 21, wherein: (i) When the elastic pad is pressed so that the thickness of the elastic pad becomes 2 mm, the repulsive force of the elastic pad is measured to be 7 kPa or more and 28 kPa or less.
24. The resilient pad of claim 21, wherein: (i) When the elastic pad is pressed so that the thickness of the elastic pad becomes 2 mm, the repulsive force of the elastic pad is measured to be 9 kPa or more and 27 kPa or less.
25. The resilient pad of claim 21, wherein: (ii) The elastic pad is compressed at a pressure of 40 kPa for 20 seconds and then has a thickness of 1.2 mm or more when the pressure is released.
26. The resilient pad of claim 21, wherein: (ii) The elastic pad is compressed at a pressure of 40 kPa for 20 seconds and then has a thickness of 2.0 mm or more when the pressure is released.
Citation Information
Patent Citations
JP1975047265A
Multi-pole ion exchange membrane electrolytic bath
CN1292043A
Novel electrolysis cell
US4340452A